Pengujian Aktivitas Antioksidan Menggunakan Metode DPPH pada Daun Tanjung (Mimusops elengi L) - Dewi Tristantini; Alifah Ismawati; Bhayangkara Tegar Pradana; Jason Gabriel Jonathan (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2016)
Mimusops elengi L is one of the plantfrom India, Sri Lanka and Burma that have potential as antioxidant which can be used to treat various disease. The main content of the ethanol extract of the leaves Mimusops elengi L which have antioxidant activity are quercetin, hentriacontane, and β-carotenewhich is a source of natural antioxidants.Extraction using reflux method by varying the extraction time 15 minutes, 30 minutes, 45 minutes, 60 minutes and 75 minutes. The extract of leaves of M. elengi were prepared in methanol. The measurement of antioxidant activity carried out using DPPH method. The result showed that the extract ethanol at 45 minutes variaty of time extraction have the highest antioxidant activity, with IC50 value were 10,6.